Shattered - Johnston, Joan, 1948- (Don Mills, Ont. : Mira Books, 2010)
"Nine years ago, Kate Grayhawk Pendleton walked into Wyatt Shaw's life--and out of it the next morning. Now Wyatt's back--and has the power to shatter Kate's future with the man she loves. By reputation, Wyatt Shaw is a brutal killer who always gets what he wants. And he wants Kate and her twin eight-year old sons. Texas Ranger Jack McKinley is hot on Wyatt Shaw's trail. The presumed heir to the D'Amato crime syndicate is threatening to steal the woman he loves. Holly McKinley is fighting to keep Jack from leaving her for another woman. Now the secret she's kept for over twenty years may save their son's life, and cost her the only man she's ever loved."--p.[4] of cover.
Series volume number from author's Web site.
Keywords: Texas Rangers -- Fiction; Murderers -- Fiction; Man-woman relationships -- Fiction; Texas -- Fiction; Romantic suspense fiction; Love stories